Seasonality in carriage of extended-spectrum β -lactamase-producing Escherichia coli and Klebsiella pneumoniae in the general population: a pooled analysis of nationwide cross-sectional studies - Wielders, C. C. H.; Van Duijkeren, E.; Van Den Bunt, G.; Meijs, A. P.; Dierikx, C. M.; Bonten, M. J. M.; Van Pelt, W.; Franz, E.; De Greeff, S. C. (Epidemiology and infection, 2020)
Infections due to extended-spectrum β -lactamase-producing Enterobacteriaceae (ESBL-E) are often preceded by asymptomatic carriage. Higher incidences in enteric infectious diseases during summer have been reported. Here, we assessed whether the presence of seasonality in intestinal ESBL- Escherichia coli / Klebsiella pneumoniae (ESBL-E/K) carriage in the general Dutch population exists. From 2014 to 2017, the faecal carriage of ESBL-E/K in healthy individuals was determined in three cross-sectional studies in the Netherlands, including 5985 subjects. Results were pooled to identify seasonal trends in prevalence (by month of sampling). Multivariate logistic regression analysis was used to calculate pooled odds ratios and 95% confidence intervals. Results were adjusted for age, sex, antibiotic use and travel. Overall prevalence of ESBL-E/K carriage was 4.3% ( n = 260 ESBL-E/K-positive), with differences between months ranging from 2.6% to 7.4%. Compared to January, the monthly prevalence of ESBL-E carriage was highest in August (OR 1.88, 95% CI 1.02–3.49) and September (OR 2.25, 95% CI 1.30–3.89). The observed monthly differences in ESBL-E/K carriage rates suggest that there is seasonal variation in exposure to ESBL-E/K other than due to travelling and antibiotic use. This should be taken into account in designing future ESBL-E prevalence studies in temperate regions.